An Examination of Stock Market Return Volatility During Overnight and Intraday Periods, 1964-1989 - Lockwood, Larry J.; Linn, Scott C. (Journal of Finance, 1990)
This paper examines the variance of hourly market returns during 1964-89. Results indicate that return volatility falls from the opening hour until early afternoon and rises thereafter, and is significantly greater for intraday versus overnight periods. Market variance is also shown to change significantly over time, rising after NASDAQ began in 1971, rising after trading in stock options began in 1973, falling after fixed commissions were eliminated in 1975, rising after trading in stock index futures was introduced in 1982, and falling after margin requirements for stock index futures became larger in 1988. Copyright 1990 by American Finance Association.